2021
DOI: 10.1021/jacs.1c03868
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Measurement to Probe Solvation Energy and Its Correlation to Lithium Battery Cyclability

Abstract: The electrolyte plays a critical role in lithium-ion batteries, as it impacts almost every facet of a battery’s performance. However, our understanding of the electrolyte, especially solvation of Li+, lags behind its significance. In this work, we introduce a potentiometric technique to probe the relative solvation energy of Li+ in battery electrolytes. By measuring open circuit potential in a cell with symmetric electrodes and asymmetric electrolytes, we quantitatively characterize the effects of concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
134
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(155 citation statements)
references
References 42 publications
8
134
0
Order By: Relevance
“…[7,8] Some researchers have reported that increasing the content of inorganics in the SEI layer is beneficial for improving its stability and mechanical strength. [9][10][11] Different strategies for modulating the Li anode interface were investigated, including the use of electrolyte additives and artificial SEI layers. [12][13][14][15][16][17][18] Among them, regulating the composition of the SEI layers by changing the solvation structure of Li + using electrolyte additives seemed simpler.…”
mentioning
confidence: 99%
“…[7,8] Some researchers have reported that increasing the content of inorganics in the SEI layer is beneficial for improving its stability and mechanical strength. [9][10][11] Different strategies for modulating the Li anode interface were investigated, including the use of electrolyte additives and artificial SEI layers. [12][13][14][15][16][17][18] Among them, regulating the composition of the SEI layers by changing the solvation structure of Li + using electrolyte additives seemed simpler.…”
mentioning
confidence: 99%
“… 31 However, the weaker solvation may lead to the decrease of inferior ionic conductivity of the electrolyte. 33 As shown in Table S1, † the ionic conductivity ( σ ) of the CDE electrolyte is 2.63 mS cm −1 . As the concentration of LiFSI increased from 0.02 M to 0.12 M, the ionic conductivity decreased from 2.50 to 2.26 mS cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…30 The stark difference for FDEE is likely due to the special Li + …F-CH2-interaction between FDEE and Li + , as suggested by the induced chemical shifts of 7 Li-NMR and 19 F-NMR (Figure 1f and Figure S6-8). 23,24,31 Such interaction apparently increases the solvating ability of FDEE (Figure S9) to reduce the anion coordination for more facial ionic conduction. 29,32 As indicated in Figure 1g, the ionic conductivity of FDEE-LHCE (~3.25 mS cm -1 ) is about twice of that in DEE-LHCE (~1.71 mS cm -1 ).…”
Section: Unique Properties Of Fdee and Reduced LI + -Anion Coordinationmentioning
confidence: 99%